Equity research lindt & sprüngli: a different perspective on chocolate - Vicente, Maria Francisca Ferreira Martins Pereira (2022)
This Equity Research aims to value Lindt & Sprüngli to determine the expected capital and dividend gains for an investor buying the stock and holding it during the year of 2022. In order to do so, an overview of the company is made as well as of its number one raw material –cocoa. Following this, a reflection on the chocolate industry is performed by discussing the peers’ performance and the industry’s future trends.